2019
DOI: 10.1101/854752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole genome sequencing analysis of the cardiometabolic proteome

Abstract: The human proteome is a crucial intermediate between complex diseases and their genetic and environmental components, and an important source of drug development targets and biomarkers. Here, we comprehensively assess the genetic architecture of 257 circulating protein biomarkers of cardiometabolic relevance through high-depth (22.5x) whole-genome sequencing (WGS) in 1,328 individuals. We discover 131 independent sequence variant associations (P<7.45×10−11) across the allele frequency spectrum, all of which… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…To evaluate the effect of diverse ancestry, we obtained statistics for a single study of 15 hematological traits from metaanalysis of five global populations [23]. To evaluate the effect of direct sequencing vs genotype imputation, we obtained statistics from two additional studies reporting WGS derived summary statistics [24,25]. We selected significant regions, merged with GTEx Whole Blood summary statistics, ran coloc and POEMColoc as described above for the UKBB summary statistics.…”
Section: Evaluating Poemcoloc On Gwas Hits and Gtex Eqtlmentioning
confidence: 99%
“…To evaluate the effect of diverse ancestry, we obtained statistics for a single study of 15 hematological traits from metaanalysis of five global populations [23]. To evaluate the effect of direct sequencing vs genotype imputation, we obtained statistics from two additional studies reporting WGS derived summary statistics [24,25]. We selected significant regions, merged with GTEx Whole Blood summary statistics, ran coloc and POEMColoc as described above for the UKBB summary statistics.…”
Section: Evaluating Poemcoloc On Gwas Hits and Gtex Eqtlmentioning
confidence: 99%
“…As samples are easy to store, collection is minimally invasive for study participants, and hundreds to thousands of molecules can be measured, plasma proteins have been investigated as biomarkers for numerous diseases 1 . The recent advances in targeted proteomics technologies have allowed thousands of circulating plasma protein levels to be measured simultaneously, even in large sample sizes [2][3][4][5][6][7][8][9] . Uncovering relationships between protein biomarkers and disease has the potential to aid in prediction of risk, diagnosis and development of new therapies for disease 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous large GWAS of plasma protein levels have discovered hundreds of associated loci, uncovered mechanisms for pQTL, causal relationships between proteins and diseases and posited how plasma protein levels may act to influence disease risk 3,4,7,8,17,18,20 . In order to maximise the potential for pQTL discovery and MR to find causal associations with disease and build on previous work, we performed genome-wide meta-analysis with the largest sample size for 184 cardiovascular-related plasma proteins.…”
Section: Introductionmentioning
confidence: 99%
“…An important issue linked to blood analysis is the underlying effect of genetics to determine stable differences in protein levels between individuals. The levels of blood proteins have previously been determined to be influenced both by genetic and environmental factors, as studied by mass spectrometry-based proteomics [1][2][3][4], nucleic-acid based assays [5][6][7][8], and immuno-based assays [9][10][11][12][13][14]. Effects based on sex [15], specific diets [15], age [16], and infections [17] have also been reported suggesting an important role for quantitative blood protein assays for individualized diagnosis of health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Suhre et al [8] analyzed the associations between protein levels and gene variants in a German cohort using SOMAscan platform and Affymetrix Array and identified 57 genetic risk loci for 42 disease end points. The PEA platform has also been used for genetic association studies, such as the identification of 16 pQTLs associated with known biomarkers [9], 79 loci for plasma protein biomarkers in cardiovascular disease [10], 8 cis-pQTL in the InCHIANTI study [11], 41 loci for the plasma levels of neurological proteins [12], and 131 independent sequence variant associations of the cardiometabolic proteome [13]. In addition, Yao et al [14] analyzed the association of protein levels and genetic factors for 16,000 pQTL variants in more than 6000 individuals in the Framingham Heart Study using Luminex multiplex immunoassays and identified 13 proteins harboring pQTL variants that match coronary disease-risk variants from GWAS.…”
Section: Introductionmentioning
confidence: 99%